Program Bincang Santai dalam Transportasi Publik - Salman Al Hafizh; Zulfe briges (Bandung Conference Series: Public Relations, 2023)
Abstract. Today Indonesia has a very rapid development of the transportation system, one of the actors behind the development of the transportation system is PT. Indonesian Railways (PT KAI or KAI). The large number of PT KAI's consumers in Indonesia have narrowed down to consumers who like and have an interest in trains, they are usually called railfans. To strengthen the lines of communication between railfans and PT KAI, PT KAI's public relations team organizes a routine activity program with railfans, namely "Casual Talk". The Casual Talk Program is a special program that provides a variety of interesting information and is the talk of many people and is packaged in a warm and relaxed manner. This study aims to determine the effectiveness of the implementation of the "Casual Talk" program held by the public relations of PT. KAI for railfans uses qualitative descriptive research methods and uses observation, interview and documentation data collection techniques. Testing the validity of the data will be carried out in three ways, namely data reduction, data display, and verification. Abstrak. Dewasa ini Indonesia memiliki perkembangan sistem transportasi yang sangat pesat, salah satu pelaku yang bergerak dibalik perkembangan sistem transportasi adalah PT. Kereta Api Indonesia (PT KAI atau KAI). Banyaknya konsumen PT KAI di Indonesia mengerucut menjadi para konsumen yang menggemari serta memiliki ketertarikan terhadap kereta api, mereka biasa disebut railfans. Untuk mempererat tali komunikasi antara railfans dengan PT KAI, humas PT KAI menyelenggarakan program kegiatan rutin bersama para railfans yaitu “Bincang Santai”. Program Bicang santai merupakan program spesial yang memberikan berbagai informasi yang menarik serta menjadi perbincangan banyak orang serta dikemas secara hangat dan santai. Penelitian ini memiliki tujuan untuk mengetahui efektifitas implementasi program "Bincang Santai" yang diadakan oleh humas PT. KAI untuk para railfans dengan menggunakan metode penelitian dekriptif kualitatif dan menggunakan teknik pengumpulan data observasi, wawancara dan dokumentasi. Uji keabsahan data akan dilakukan dengan tiga cara yaitu reduksi data, data display, dan verification.